2014
DOI: 10.1016/j.jacc.2014.06.1175
|View full text |Cite
|
Sign up to set email alerts
|

Translating Stem Cell Research to Cardiac Disease Therapies

Abstract: Over the past 2 decades, there have been numerous stem cell studies focused on cardiac diseases, ranging from proof-of-concept to phase 2 trials. This series of articles focuses on the legacy of these studies and the outlook for future treatment of cardiac diseases with stem cell therapies. The first section by Rosen and Myerburg is an independent review that analyzes the basic science and translational strategies supporting the rapid advance of stem cell technology to the clinic, the philosophies behind them,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 115 publications
(164 reference statements)
0
61
0
Order By: Relevance
“…Despite the promise of MSC, linking preclinical CCT data in small animals with data in large animals and, eventually, humans has been an enormous challenge (8) In Vitro Bioluminescence Imaging of MSC-TF To determine levels of reporter gene activity, MSC-TF populations were assessed for FLUC2 activity. The following three populations were analyzed with bioluminescence imaging: (a) high-expressing MSC-TF from the first sort, (b) high-expressing MSC-TF from the second sort, and (c) highexpressing MSC-TF from the third sort.…”
Section: Advances In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the promise of MSC, linking preclinical CCT data in small animals with data in large animals and, eventually, humans has been an enormous challenge (8) In Vitro Bioluminescence Imaging of MSC-TF To determine levels of reporter gene activity, MSC-TF populations were assessed for FLUC2 activity. The following three populations were analyzed with bioluminescence imaging: (a) high-expressing MSC-TF from the first sort, (b) high-expressing MSC-TF from the second sort, and (c) highexpressing MSC-TF from the third sort.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Studies of CCT after treatment of mouse MI with MSC-TF indicated survival in the MI condition and significant differences in signal compared with MSC with no MI on day 14 (P = .016), and this trend was confirmed with ex vivo luciferase assays. Having achieved the required in clinical trials (8,28) have limited CCT implementation, in part due to the inability to link small-animal and large-animal preclinical data to clinical data. To address this, we designed a two-part study to use multimodality imaging as an enabling tool to analyze MSC for CCT and to achieve a specific small-animal imaging endpoint prior to the large-animal study.…”
Section: Molecular Imaging: Cardiac Cell Imaging In Micementioning
confidence: 99%
“…pluripotent stem cells (PSCs), bone-marrow derived stem cells, skeletal myoblasts or cardiac stem cells] possessing cardiogenic potential have shaped the notion of stem cell-based cardiac restorative REVIEW therapy [7,8] . Despite much knowledge has been gained through numerous basic researches, clinical investigations in cardiac stem cell therapy using somatic stem cells with relatively small cohort still lack sufficient conclusive results to support full-scale implementation of the treatments [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell-based therapies in small animal models have yielded promising but variable results [6][7][8]. Several studies have supported the use of large animals, such as pigs, with a similar heart size and physiology to humans, to monitor the survival, engraftment, and efficacy of transplanted hESC-derived cardiac cells [2][3][4][9][10][11][12]. However, the clinical application of cellbased therapies will require noninvasive imaging approaches that will allow in vivo monitoring of transplanted cells [7,8,13,14].…”
Section: Introductionmentioning
confidence: 99%